MANAGEMENT OF MANDIBULAR PARASYMPHYSIS FRACTURE WITH EXTRUSIVE LUXATION: A CASE REPORT - Janna, Syadira Putri; Erpita, Andria Fadli; Mirza, Salsabilla Milatul (Universitas Baiturrahmah, 2025)
Mandibular parasymphysis fractures account for approximately 15% of all mandibular fractures, often resulting from high-impact trauma directed upward or obliquely to the lower face. Such injuries may be associated with traumatic dental injuries, including extrusive luxation, which is characterized by loosening and partial displacement of a tooth from its socket. We report a case of a 20-year-old male referred to RSUD Dr. Achmad Mochtar following a motorcycle accident 7 days prior to admission. The patient presented with chin pain, limited mouth opening, masticatory difficulty, and mobility with sensitivity of the maxillary anterior tooth. Clinical examination revealed an abrasion on the left cheek and sutured laceration on the left upper labial and mental regions, a posterior open bite on the right side, and extrusive luxation of tooth 22. Step deformity and mobility were noted in the right mandibular region at teeth 43–44. Radiographic evaluation confirmed a radiolucent fracture line between teeth 43 and 44. The socket of tooth 22 appeared empty apically, with widening of the periodontal ligament space. Diagnosis of mandibular parasymphysis dextra fracture with extrusive luxation of tooth 22 was established. Management consisted of repositioning and stabilization of tooth 22, followed by closed reduction and internal fixation (CRIF) using arch bar and intermaxillary fixation. Postoperative outcomes showed satisfactory occlusion and stable adaptation of tooth 22 in its socket. This case highlights the importance of comprehensive evaluation and timely management of mandibular fractures associated with dental luxation to restore function and prevent long-term complications.